THE CULTURED ISLAM: THE BOUNDARY OF ISLAMIC IDENTITY BETWEEN THE MINANGKABAU AND MANDAILING ETHNICS - Kamal, Muhiddinur; Rozi, Syafwan (El-HARAKAH (TERAKREDITASI), 2020)
The relationship between Islam and culture was compatible and not antonym. Islam was a dynamic product and a long-term process of giving and receiving in the dynamics and social interaction of its people. The contradiction between the ideal demands of religion and the demands of tradition and the social reality of society was a crucial problem faced by any religion in the world, but adjustments to social reality always occurred. The Islamic community in the Minangkabau border area was a cultural community that had and continued to confirm genuinely and became accommodative openness in resolving the contradictions of adat and Islam which were in principle very apparent in their cultural systems. Through ethnographic research, this article revealed that conflicts and contradiction between the normative concepts of Islam and adat always occurred in societies inhabited by the Minangkabau and Mandailing ethnic groups, especially related to marriage, kinship, inheritance system and communal property ownership. But the process always ran elegantly and attractively through the dialectics and dynamics of the people. Thus, Islam was culturally acculturated with Minangkabau culture and Mandailing culture and formed a distinctive cultural Islamic identity in the border area.Â Relasi Islam dengan kebudayaan adalah sesuatu yang selaras dan bukan antonim. Islam adalah produk dinamis dan proses dalam jangka panjang, yang saling memberi dan menerima dalam dinamika dan interaksi sosial masyarakatnya. Kontradiksi antara tuntutan ideal agama dan tuntutan tradisi serta realitas sosial masyarakat merupakan persoalan krusial yang dihadapi agama apapun di dunia, namun penyesuaian realitas sosial selalu terjadi. Masyarakat Islam di daerah perbatasan Minangkabau adalah komunitas budaya yang telah dan terus melakukan konfirmitas secara genuine serta akomodatif terbuka dalam menyelesaikan kontradiksi adat dan Islam yang secara prinsip sangat kentara dalam sistem budaya mereka. Melalui penelitian etnografi, artikel ini mengungkap bahwa konflik dan pertentangan antara konsep normatif Islam dengan adat selalu terjadi dalam masyarakat yang dihuni oleh etnik Minangkabau dan etnik Mandailing, terutama masalah perkawinan, kekerabatan, sistem kewarisan dan kepemilikan harta komunal. Namun proses itu selalu berjalan secara elegan dan atraktif melalui dialektika dan dinamika masyarakatnya. Sehingga, Islam secara kultur berakulturasi dengan budaya Minangkabau dan budaya Mandailing dan membentuk identitas Islam kultur yang khas di daerah perbatasan